2018
DOI: 10.1177/0886260518780408
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use After Unwanted Sexual Experiences in Undergraduates: A Comprehensive Evaluation of Factors Related to the Decision to Seek Help

Abstract: The risk for sexual victimization in college is high, and although there can be significant mental and physical consequences for the survivor, resource utilization for this issue is extremely low. The current study used the frameworks of both the ecological model and the theory of planned behavior to examine factors related to resource use in undergraduate survivors of unwanted sexual experiences. The sample consisted of 217 undergraduates who reported at least one unwanted sexual experience while in college (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
(41 reference statements)
2
28
0
Order By: Relevance
“…Most studies (n = 25) found a positive relationship, indicating that more positive attitudes towards help‐seeking are related to higher intentions to seek help and increased help‐seeking behaviour. Fleming et al (), and Miville and Constantine () could not confirm a relationship. Chang () found a positive relationship for psychological help‐seeking, but no relationship for academic‐ and career‐related help‐seeking.…”
Section: Resultsmentioning
confidence: 89%
“…Most studies (n = 25) found a positive relationship, indicating that more positive attitudes towards help‐seeking are related to higher intentions to seek help and increased help‐seeking behaviour. Fleming et al (), and Miville and Constantine () could not confirm a relationship. Chang () found a positive relationship for psychological help‐seeking, but no relationship for academic‐ and career‐related help‐seeking.…”
Section: Resultsmentioning
confidence: 89%
“…Rates of reporting to law enforcement have ranged from 0.6–13%, with most studies finding that fewer than 10% report to the police (e.g., Fisher et al, 2003; Krebs et al, 2007; Lindquist et al, 2013; Walsh et al, 2010; Wolitzky-Taylor et al, 2011). Only a few studies have looked at rates of reporting to campus law enforcement specifically, and the rates are generally very low: approximately 5% of survivors report the assault to Campus Police (e.g., 5.3% in Fleming et al, 2018; 4% in Nasta et al, 2005). In addition to reporting to the police, college students have the option to report the assault through their institution’s disciplinary process.…”
Section: Sexual Assault Survivors’ Use Of Formal Supportsmentioning
confidence: 99%
“…Department of Education, 1997, 2001, 2011). However, researchers have found that very few survivors report via these formal university procedures (e.g., to a “Title IX Office”), with rates ranging from 0–4.3% (e.g., Fleming et al, 2021; Khan et al, 2018; Lindquist et al, 2013).…”
Section: Sexual Assault Survivors’ Use Of Formal Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study responded to both closed-ended surveys and open-ended free response questions. Quantitative outcomes regarding predictors of help-seeking behavior in this sample have been reported elsewhere (Fleming, Lynch, Hakas, & Belanger, 2018), and the current analysis focuses on the open-ended responses. Participants were asked to respond to the following prompts:…”
Section: Methodsmentioning
confidence: 99%